2020
DOI: 10.26848/rbgf.v13.3.p1094-1105
|View full text |Cite
|
Sign up to set email alerts
|

Análise do Desempenho da Estimativa de Precipitação do Produto CHIRPS para Sub-Bacia do Rio Apeú, Castanhal-PA

Abstract: A precipitação é entendida como toda água oriunda do meio atmosférico que alcança a superfície terrestre e estudos sobre o comportamento e distribuição da precipitação em bacias hidrográficas são fundamentais para o conhecimento dos processos hidrológicos de uma região ou bacia hidrográfica. Assim, o presente estudo, tem como objetivo avaliar o desempenho dos dados de precipitação estimados pelo produto CHIRPS, para sub-bacia do rio Apeú em relação aos dados observacionais das estações meteorológicas do INMET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
1
11
1
1
Order By: Relevance
“…E. R. M. D. Silva et al (2020) also found a good correlation between CHIRPS estimates and ANA data in the Apeú River subbasin in the state of Pará, Amazon, Brazil. The results found by Pessi et al (2019) and E. R. M. D. Silva et al (2020) are consistent with the present study, in which it appears that for the state of Mato Grosso, the highest value of r was determined through the product, and in the state of Pará, the highest value of r was determined using the product CHIRPS. The index of agreement values were all higher than 0.75, which illustrates a good representativeness of the satellite estimates in the Amazon region.…”
Section: Equation Ideal Valuementioning
confidence: 53%
See 2 more Smart Citations
“…E. R. M. D. Silva et al (2020) also found a good correlation between CHIRPS estimates and ANA data in the Apeú River subbasin in the state of Pará, Amazon, Brazil. The results found by Pessi et al (2019) and E. R. M. D. Silva et al (2020) are consistent with the present study, in which it appears that for the state of Mato Grosso, the highest value of r was determined through the product, and in the state of Pará, the highest value of r was determined using the product CHIRPS. The index of agreement values were all higher than 0.75, which illustrates a good representativeness of the satellite estimates in the Amazon region.…”
Section: Equation Ideal Valuementioning
confidence: 53%
“…In Brazil, Pessi et al (2019) observed a strong correlation between precipitation estimates through the TRMM satellite and observations from the network of conventional rainfall gauge stations for the entire region of the state of Mato Grosso. E. R. M. D. Silva et al (2020) also found a good correlation between CHIRPS estimates and ANA data in the Apeú River subbasin in the state of Pará, Amazon, Brazil. The results found by Pessi et al (2019) and E. R. M. D. Silva et al (2020) are consistent with the present study, in which it appears that for the state of Mato Grosso, the highest value of r was determined through the product, and in the state of Pará, the highest value of r was determined using the product CHIRPS.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…It is also emphasized that the efficiency of CHIRPS product was highlighted by Silva et al (2020) when the performance of product's precipitation estimative to sub-basin of Apau River, Castanhal (PA) was analyzed. The results evidenced that the CHIRPS achieved to replicate with good precision the seasonal variability of precipitation on the region of interest, with significatively correlations varying between 0.86 and 0.99 with pluviometers data.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, research using data from satellite rainfall products is expanding. These studies sought to analyze and evaluate satellite data both for Brazil as a whole [13,17] and for certain regions or watersheds [13,18,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%